2021
DOI: 10.3390/ijms22168542
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oxygen Carrier (M101) Attenuates Ischemia-Reperfusion Injuries during Static Cold Storage in Steatotic Livers

Abstract: The combined impact of an increasing demand for liver transplantation and a growing incidence of nonalcoholic liver disease has provided the impetus for the development of innovative strategies to preserve steatotic livers. A natural oxygen carrier, HEMO2life®, which contains M101 that is extracted from a marine invertebrate, has been used for static cold storage (SCS) and has shown superior results in organ preservation. A total of 36 livers were procured from obese Zucker rats and randomly divided into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Similar results were obtained in pancreas preservation 24,25 . Studies in rat livers show that adding the biological oxygen carrier M101 to the SCS solution prevents ATP depletion and attenuates IRI compared with grafts preserved by SCS without an oxygen carrier 26,27 . Minor et al have extensively studied the effects of gaseous insufflation, which includes the delivery of oxygen via a catheter in the caval vein during several hours of SCS preservation 28–30 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similar results were obtained in pancreas preservation 24,25 . Studies in rat livers show that adding the biological oxygen carrier M101 to the SCS solution prevents ATP depletion and attenuates IRI compared with grafts preserved by SCS without an oxygen carrier 26,27 . Minor et al have extensively studied the effects of gaseous insufflation, which includes the delivery of oxygen via a catheter in the caval vein during several hours of SCS preservation 28–30 .…”
Section: Discussionmentioning
confidence: 67%
“… 24 , 25 Studies in rat livers show that adding the biological oxygen carrier M101 to the SCS solution prevents ATP depletion and attenuates IRI compared with grafts preserved by SCS without an oxygen carrier. 26 , 27 Minor et al have extensively studied the effects of gaseous insufflation, which includes the delivery of oxygen via a catheter in the caval vein during several hours of SCS preservation. 28 , 29 , 30 After preclinical studies, results from a prospective clinical trial demonstrated a positive effect of gaseous insufflation on the development of early allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, C3 specific inhibitors using peptides and nanobodies platforms have been developed and clinical trials conducted in a large panel of diseases including periodontal inflammation and COVID-19 with AMY-101 ( 27 , 28 ), in paroxysmal nocturnal haemoglobinuria with pegcetacoplan ( 29 ), and in acute antibody-mediated graft injury and age-related macular degeneration with Cp40 ( 30 , 31 ). In addition to its anti-complement properties, M101 has original characteristics including oxygen carrier, anti-inflammatory, anti-bacterial, and superoxide dismutase antioxidant properties ( 32 , 33 ). It is further notable that no immunological, allergic or prothrombotic effects were associated with M101 injection, and, in contrast to cell-free HbA, M101 did not lead to hypertension, myocardial infarction, renal damage, complement activation or tissue toxicity, which supports systemic usage ( 3 , 8 , 9 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This transient restoration of oxygenation achieved with M101 presumably contributes to maintaining liver mitochondrial machinery to function at basal levels, thus avoiding the accumulation of succinate during cold ischemia, according to Schlegel’s mechanism [ 25 ]. Furthermore, the M-101 additive is also useful for fatty liver static preservation when combined with HOPE [ 47 ], but additional studies should investigate in depth its usefulness in maintaining graft quality when longer cold storage periods are applied, especially in vulnerable organs (DCD donors, pancreas, and fatty liver grafts).…”
Section: New Additives For Improving Cold Static Preservation: Oxygen...mentioning
confidence: 99%
“…For years, static preservation has been based on the principles of hypothermic and static storage; however, the limitation of oxygen supply is serious for graft survival, given that the conditions proposed for static preservation are far from physiological. The use of HOPE is very promising [ 67 , 68 , 69 , 70 , 71 , 72 ], as well as gas additives or hemoglobins such as M-101 that, combined with further HOPE, could be an alternative method to palliate the deficient oxygenation of the graft during static preservation conditions [ 46 , 47 ].…”
Section: Some Considerations and Concluding Remarksmentioning
confidence: 99%